AKUNTANSI SOSIAL SEBAGAI ALAT BANTU PELAPORAN PERTANGGUNGJAWABAN SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) - Dian Imanina Burhany (Universitas Palangka Raya, 2020)
Corporate social responsibility (CSR) is a central issue in business nowdays. Because of pressure of their stakeholder in one side and with understanding about the important of CSR for sustainability in the other side, most firms now not only care about ec onomic asspect of their business but also care about other aspects that are social and environmental or many others else that are affected by firms operational. To disclose and report CSR, firms need social accounting. Social accounting can help firms in formulating and generating corporate social reporting so that stakeholder can read, evaluate and mak e important decisions about the firms.